Seconoriridone A: A C16-seco-noriridal derivative with a 5/5/7 tricyclic skeleton from Belamcanda chinensis. Issue 13 (28th March 2019) - Li, Jiayuan; Ni, Gang; Liu, Yanfei; Mai, Zhenpeng; Wang, Renzhong; Yu, Dequan
Graphical abstract: Highlights: Seconoriridone A, a C16 - seco -noriridal, was isolated from Belamcanda chinensis . The absolute configuration of1 was assigned by quantum chemical calculations. It is the first time to report the C16 - seco -noriridal. Compound1 exhibited moderate anti-inflammatory activities. Abstract: Seconoriridone A (1 ), a novel C16 - seco -noriridal with a 5/5/7 tricyclic scaffold, was isolated from the rhizome of Belamcanda chinensis . Its structure and absolute configuration were determined by NMR spectroscopy and quantum chemical calculations. Notably, seconoriridone A featured a 2-butanonyl moiety with oxidative cleavage of the conventionally multisubstituted cyclohexane ring of iridals. Seconoriridone A was a mixture of C-14 epimers in the presence of hemiacetal. The plausible biosynthetic pathway for1 was deduced.